Bronchoalveolar Lavage Fluid Cellular and Haematological Changes in Different Types of Caprine Pneumonia (Nigerian Journal of Physiological Sciences, 2021)
Summary: Goats in the tropics are often reared under the traditional extensive and semi-intensive management systems. These and other factors influence the pattern of pneumonia complex in goats. We investigated the bronchoalveolar lavage fluid (BALf) cellular changes and haematological response in different types of caprine pneumonia in Nigeria. Haematological indices and BALf cells were analysed from 300 goats randomly selected from 700 goats comprising different breed, age and body scores. The pneumonia status was well characterised using standard pathological tools. Data is summarized as Mean ± SEM and compared using non-parametric statistics at 5% significance. There was leukocytosis in the pneumonic animals. The overall lavage recovery rate was 55.5%. The differences in Haemoglobin concentration, and Lymphocyte-Neutrophil ratio were significant (p
Keywords: Bronchoalveolar lavage; Haematology; Pneumonia; Comparative; Caprine